Dangers lurking in the OECD tax proposals - Gary Clyde Hufbauer (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
As the OECD strives to rearrange international corporate taxation, a word of caution is in order. The first "Pillar", if adopted, will spawn a confusing array of new taxes; the second "Pillar" will spur fresh loopholes as national legislatures assert their sovereign prerogatives.
Keywords: 330